Analysis of Factors Affecting The Income of Souvenir Traders At Kumbasari Market, Denpasar City - Ariastha Satrya Wicaksana; Made Kembar Sri Budhi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Traditional markets serve a crucial function in fulfilling the community’s needs by facilitating transactions. As a selling place, traditional markets serve as a key source of income. Observing this phenomenon, this study investigates the factors that influence trader income. The objective is to explain how capital, business duration, product variety, and the use of QRIS affect traders’ income. The grand theory underpinning this research is the theory of income. This study was conducted among souvenir traders at Kumbasari Market, Denpasar, using a multivariate analysis approach with a sample size of 111 traders. Data were collected through offline surveys using questionnaires. The analysis technique employed was multiple linear regression. The results show that capital, business duration, product variety, and the use of QRIS have both partial and simultaneous positive and significant effects on trader income. Among these variables, capital exerts the greatest influence. The findings of this study are expected to enrich the development of economic science, particularly in relation to income, and serve as a reference for traders in formulating strategies to improve performance.